Association of Elevated Heart Risk Score with Myocardial Infarction in Patients with Chest Pain: Elevated Heart Risk Score in Myocardial Infarction - Ghulam Rasool, Ayaz; Ayaz , Asia (Pakistan Journal of Health Sciences, 2023)
The HEART score is a widely used diagnostic tool in patients with chest pain. This tool is a very effective method for the stratification of patients with chest pain in the emergency department. It is composed of five components, i.e., history, ECG, age risk factors and troponins. Objective: To assess the importance of HEART score in our population. Methods: This study was conducted at emergency department of Ziauddin University Hospital, Karachi, Pakistan from 01 January 2021 to 30 June 2022. A cohort study of the HEART risk score in myocardial infarction (MI) patients presented with chest pain was conducted. 244 patients were selected by consecutive sampling and distributed into two groups i.e., non-exposed (HEART risk score 0-3) and exposed group (HEART risk score ≥ 4). The HEART risk score was calculated and patients were followed for the next 48 hours. Results: Patients of both groups were monitored for forty-eight hours and the results were myocardial infarction (MI) in 1 (0.8%) patient and 86 (70.5%) patients in group A (low risk) and group B (high risk) respectively. One patient (0.8%) in each group A (low risk) and in group B (high risk) left against medical advice (LAMA). One hundred twenty (98.4%) patients in group A and thirty-five (28.7%) patients in group B (high risk) were discharged. No patient (0.0%) expired in group A (low risk) and in group B (high risk) respectively. Conclusions: It was concluded from the study that the HEART risk score is very much helpful as a diagnostic tool in patients with chest pain, presented in the emergency